(untitled) (Research, Society and Development, 2020)
Currently, there is a deficiency in scientific disclosures, with the advent of new communication technologies, the information is disseminated quickly but not always correctly. With this, in this work we formulated a set of comics with an accessible language for the dissemination of basic concepts of Physics and Astronomy. For the evaluation of the comics, these were used in a pilot group of primary and secondary education. Comic books are great teaching-learning tools especially for high school students who have reported a greater interest in playful learning activities.